Stabilin-1+/SMA- macrophages in diagnostics of postinfarction tissue inflammation associated with adverse cardiac remodeling in patients with myocardial infarction. (25th November 2020) - Gombozhapova, A; Rogovskaya, Y; Rebenkova, M; Kzhyshkowska, J; Ryabov, V
Abstract: Introduction: Molecular biomarkers of monocytes/macrophages identified to date have provided advanced diagnostic capabilities. We have accumulated a large amount of knowledge related to the role of innate immune response in the development of postinfarction cardiac remodeling. However, there is no significant advancement in clinical studies. Purpose: The purpose was to assess prospects of macrophage biomarkers in diagnostics of postinfarction tissue inflammation associated with adverse cardiac remodeling in patients with myocardial infarction (MI). Methods: The study included 41 patients with MI type 1, died in 2013–2014. We used a biobank of tissue samples for analysis. Group 1 (n=24) comprised patients who died within 72 hours of MI (the inflammatory phase), group 2 (n=17) comprised patients who died 4–28 days after MI (the regenerative phase). Macrophage infiltration in the heart was assessed by double immunofluorescence. We used stabilin-1 as a marker of M2 macrophages, while α-smooth muscle actin (α-SMA) was considered as a marker of cell transdifferentiation. Cells were counted in the infarct (IA) and non-infarct area (NIA). Morphological determination of adverse cardiac remodeling was based on the ratio of heart size, in particular, length/width ratio that was <1.1. Results: We identified subpopulations of stabilin-1+/α-SMA− and stabilin-1+/α-SMA+ macrophages. In the IA the number of stabilin-1+/α-SMA− macrophages was lower during the inflammatory phase than during the regenerative phase (Table 1). The calculation of sensitivity and specificity of stabilin-1+/α-SMA− macrophages in the NIA for predicting of adverse cardiac remodeling has shown following: AUC=0.96, p<0.001. The cut-off value was 18 cells/mm 2 . The ROC curve is presented in Figure 1. Conclusions: We identified that number of stabilin-1+/α-SMA− macrophages in the NIA ranged from 0 to 18 cells/mm 2 was associated with adverse cardiac remodeling. The presence of stabilin-1+/α-SMA+ macrophages could indicate persistent tissue inflammation and possibility of macrophage transdifferentiation and plasticity. Our study supports prospects for implementation of macrophage biomarkers in clinical practice that might become a breakthrough in the development of new methods for management of MI and following complications. Funding Acknowledgement: Type of funding source: None